Biased under-reporting of research reflects biased under-submission more than biased editorial rejection [v1; ref status: indexed, http://f1000r.es/ViIqTX] - Iain Chalmers; Kay Dickersin (F1000Research, 2013)
Stephen Senn challenges Ben Goldacre’s assertion in ‘Bad Pharma’ that biased editorial acceptance of reports with ‘positive’ findings is not a cause of biased under-reporting of research. We agree with Senn that biased editorial decisions may contribute to reporting bias, but Senn ignores the evidence that biased decisions by researchers to submit reports for possible publication are the main causes of the problem.